Challenges facing post-war tourism development - Ladki, Said M. (1997)
This paper explores the issues and challenges that are facing Lebanon as it attempts to reposition itself as a leading tourism destination in the post-war years. A discussion about the Lebanese government reconstruction plan and its role in shaping tourism policies is offered. A discussion about post-war tourism development in Lebanon is offered.